Evaluation of Intraocular Pressure After Water Drinking Test in Patients with Unilateral Hemifacial Spasm - Low JR (Dove Medical Press, 2020)
Jin Rong Low,1– 3 Chee Wai Wong,1,3– 6 Jing Liang Loo,1,3,5– 8 Dan Milea,3,5,7,8 Shamira A Perera,1– 3,5 Yi Fang Lee,3,9 Si Rui Ng,1– 3 Mani Baskaran,2,3,5 Monisha Esther Nongpiur,2,3,5 Sharon Lee Choon Tow1,3,5– 8 1Department of Cataract and Comprehensive Ophthalmology, Singapore National Eye Centre, Singapore; 2Department of Glaucoma, Singapore National Eye Centre, Singapore; 3Singapore Eye Research Institute, Singapore; 4Department of Surgical Retina, Singapore National Eye Centre, Singapore; 5Ophthalmology and Visual Sciences Academic Clinical Program, Duke-NUS Medical School, Singapore; 6Department of Ophthalmology, National University of Singapore, Singapore; 7Department of Neuro-Ophthalmology, Singapore National Eye Centre, Singapore; 8Neuroscience and Behavioral Disorders Program, Duke-NUS Medical School, Singapore; 9Department of Training and Education, Singapore National Eye Centre, SingaporeCorrespondence: Sharon Lee Choon Tow Tel +65 6322 7443Fax +65 6333 8339Email sharon.tow.l.c@singhealth.com.sgPurpose: The aim of the study is to examine the baseline intraocular pressure (IOP) and its changes after performing a water drinking test (WDT) in patients with unilateral hemifacial spasm (HFS).Patients and Methods: In this prospective observational study, patients aged 21 years and above diagnosed with unilateral HFS were recruited from the Singapore National Eye Centre between January 2015 and August 2016. The unaffected eye of each patient served as a matched control. An interviewer-administered standardized questionnaire on HFS symptoms and ophthalmic examination was performed. Automated perimetry, optical coherence tomography (OCT) of the optic nerve head, color disc stereophotography and water drinking test (WDT) were done. The primary outcome measure was the difference in IOP between eyes affected by HFS and fellow eyes at baseline and at 15, 30 and 45 minutes of the WDT.Results: Fifty-four patients with unilateral HFS were included. Mean age was 59.8± 9.9 years (range, 37.0– 84.0). Of these, 54% were female and 94% were Chinese. Mean baseline IOP was significantly higher in eyes with HFS (13.9± 3.1mmHg) compared to fellow eyes (13.3± 2.8mmHg) (p=0.008). There was no significant difference in absolute or percentage change in IOP from baseline between the 2 groups at 15, 30 and 45 minutes of the WDT. Mean vertical cup–disc ratio (VCDR) on clinical examination was significantly higher in eyes with HFS (0.5± 0.2) compared to fellow eyes (0.4± 0.2) (p=0.02). There was no significant difference between the groups for visual field parameters and mean retinal nerve fiber layer thickness on OCT.Conclusion: Hemifacial spasm is associated with a small but significant difference in mean baseline IOP and VCDR between affected and fellow eyes. However, when eyes affected by HFS and fellow eyes were challenged with the WDT, both responded in similar ways.Keywords: glaucoma, hemifacial spasm, intraocular pressure, water drinking test